The use of ICT resources to transform teaching at secondary schools in the Bojanala district, Northwest province - Abueng Rachael Molotsi (South African Journal of Education, 2022)
In the study reported on here I investigated how teachers used available information and communications technology (ICT) resources to transform teaching and learning in the Bojanala district in the Northwest province of South Africa. The Technological Pedagogical Content Knowledge (TPACK) framework enabled understanding of how the use of available ICT resources transforms teaching and learning. I adopted a qualitative, multiple case study research design which was grounded in the interpretive paradigm. Eight teachers were purposefully sampled – 6 men and 2 women. Semi-structured interviews, non-participant observation and document analysis were the data collection strategies. Data analysis was done according to Creswell’s 4 pillars of data analysis. Ethics was maintained using voluntary participation, informed consent, confidentiality, and anonymity. The results reveal limited use of ICT resources to transform teaching. It is recommended that ongoing, in-service training on using ICT resources should be done to assist teachers to transform their lesson delivery. Again, schools should be provided with ICT policies to guide them on how to transform teaching using ICT resources.